Predictors of Job Stress Among Southern Correctional Staff. (March 2020) - Lambert, Eric G.; Keena, Linda D.; Haynes, Stacy H.; May, David; Leone, Matthew C.
Job stress is a problem in corrections. Although the very nature of correctional work is stressful, workplace variables also contribute to correctional staff job stress. The job demands-resource model holds that job demands increase negative outcomes (e.g., job stress) and decrease positive outcomes (e.g., job satisfaction), whereas job resources help increase positive outcomes and decrease negative outcomes. An ordinary least squares regression analysis of self-reported survey data from 322 staff at a Southern prison indicated that input into decision-making and quality supervision had statistically significant negative effects on job stress, whereas role overload and fear of victimization had significant positive effects. Instrumental communication, views of training, and role clarity all had nonsignificant associations with stress from the job in the multivariate analysis. The results partially supported the job demands-resources model; however, the specific work environment variables varied in terms of their statistical significance. Correctional administrators need to be aware of the contribution that workplace variables have on job stress and make changes to reduce staff job stress.